IL-10 production by granulocytes promotes Staphylococcus aureus craniotomy infection - Gunjan Kak; Zachary Van Roy; Cortney E. Heim; Rachel W. Fallet; Wen Shi; Axel Roers; Bin Duan; Tammy Kielian (Journal of Neuroinflammation, 2023)
Abstract Background Treatment of brain tumors, epilepsy, or hemodynamic abnormalities requires a craniotomy to access the brain. Nearly 1 million craniotomies are performed in the US annually, which increase to ~ 14 million worldwide and despite prophylaxis, infectious complications after craniotomy range from 1 to 3%. Approximately half are caused by Staphylococcus aureus (S. aureus), which forms a biofilm on the bone flap that is recalcitrant to antibiotics and immune-mediated clearance. However, the mechanisms responsible for the persistence of craniotomy infection remain largely unknown. The current study examined the role of IL-10 in promoting bacterial survival. Methods A mouse model of S. aureus craniotomy infection was used with wild type (WT), IL-10 knockout (KO), and IL-10 conditional KO mice where IL-10 was absent in microglia and monocytes/macrophages (CX3CR1 Cre IL-10  fl/fl ) or neutrophils and granulocytic myeloid-derived suppressor cells (G-MDSCs; Mrp8 Cre IL-10  fl/fl ), the major immune cell populations in the infected brain vs. subcutaneous galea, respectively. Mice were examined at various intervals post-infection to quantify bacterial burden, leukocyte recruitment, and inflammatory mediator production in the brain and galea to assess the role of IL-10 in craniotomy persistence. In addition, the role of G-MDSC-derived IL-10 on neutrophil activity was examined. Results Granulocytes (neutrophils and G-MDSCs) were the major producers of IL-10 during craniotomy infection. Bacterial burden was significantly reduced in IL-10 KO mice in the brain and galea at day 14 post-infection compared to WT animals, concomitant with increased CD4+ and γδ T cell recruitment and cytokine/chemokine production, indicative of a heightened proinflammatory response. S. aureus burden was reduced in Mrp8 Cre IL-10  fl/fl but not CX3CR1 Cre IL-10  fl/fl mice that was reversed following treatment with exogenous IL-10, suggesting that granulocyte-derived IL-10 was important for promoting S. aureus craniotomy infection. This was likely due, in part, to IL-10 production by G-MDSCs that inhibited neutrophil bactericidal activity and TNF production. Conclusion Collectively, these findings reveal a novel role for granulocyte-derived IL-10 in suppressing S. aureus clearance during craniotomy infection, which is one mechanism to account for biofilm persistence.